Hubungan Faktor Risiko Obesitas dengan Kejadian Hipertensi di Wilayah Pelabuhan Harbour Bay Tahun 2024 - Rosaline Darwis (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
Hypertension is a health problem that is often found in society with a prevalence in Indonesia of 30.8%, is one of the non-communicable diseases (NCDs) that are still a health problem in Indonesia because of their contribution to cardiovascular disease as a contributor to morbidity and mortality in society. This study aims to analyze the relationship between age, gender and obesity status with the incidence of hypertension, through a cross-sectional approach. The study was conducted on 219 respondents using a total sampling technique. The data obtained were analyzed univariately and bivariately. The results of the univariate analysis showed that the percentage of hypertension was 18.72% and the percentage of obesity was 40.2%. The results of the bivariate analysis using the Chi square test produced a significance level of p-value of 0.000 (significant) between age and obesity with a PR value of 3.47 (CI 1.22-9.87) for the age group above 54 years, and a PR value of 2.66 (CI 1.21-5.81) for the age group 46-54 years (with the age group 18-45 years as a reference). The results of the bivariate analysis using the Chi square test between gender and obesity produced a p-value of 0.0040 with a PR of 0.45. The results of the chi square test between obesity and hypertension were proven to be statistically significant with a PR of 1.90, meaning that respondents with obesity had a 1.9 times greater risk of suffering from hypertension than people without hypertension.